PENGARUH LITERASI EKONOMI DAN GAYA HIDUP TERHADAP PERILAKU KONSUMTIF MAHASISWI PENDIDIKAN EKONOMI STKIP YPM BANGKO - Saftia Wulandari, Angra Melina, (SJEE (Scientific Journals of Economic Education), 2018)
AbstractThis study aims to prove (1) Effect of Economic Literacy on Consumptive Behavior, (2) Effect of Lifestyle on Consumptive Behavior (3) Effect of economic and lifestyle literacy on Consumtive behavior of STKIP YPM Bangko Economics Education student. Research on student of study program of Economics STKIP YPM Bangko.  The research approach that will be used in this research is quantitative approach, while the method used is survey method. This study was analyzed by using multiple regression analysis. The study population was 108 people. Sampling using proportional random sampling. The number of selected samples is 85 people. Data collection using questionnaires and documentation. The data were processed using multiple regression. The result of the research shows that (1) Economic Literation has a significant influence on consumptive behavior in STKIP YPM Bangko STKIP economic student, (2) Lifestyle has significant influence on consumptive behavior on STKIP YPM Bangko economic education student and (3) Economic Literacy and Lifestyle has a significant influence on consumptive behavior in STKIP YPM Bangko's economic education studentsKeywords : Economic Literacy, Lifestyle, Consumptive Behavior.